English English - Devina Siti Hafsah; Nurfina Aznam; Eli Rohaeti (Jurnal Penelitian Pendidikan IPA, 2024)
The digital age has transformed education. In the context of chemistry education, particularly in the complex topic of salt hydrolysis, the integration of technology offers innovative solutions to enhance student learning. This study aims to develop and determine the effectiveness of Electronic Student Worksheets (E-LKPD) based on Problem-Based Learning (PBL) in improving students' learning motivation and problem-solving skills in the topic of salt hydrolysis. Through Research and Development (R&D) using the 4D model, the developed E-LKPD in Flipbook format has been validated by material and media experts with high validity values of 0.96 and 0.89 and has received a positive response from students of 80.12%. The research results show that the use of E-LKPD significantly increases students' learning motivation (45%) and problem-solving skills (75%). This indicates that PBL-based E-LKPD is an effective learning media for the topic of salt hydrolysis.